Does corporate and country corruption risk affect CEO performance? A study of the best-performing CEOs worldwide. Issue 2 (April 2022) - La Rosa, Fabio; Bernini, Francesca; Terzani, Simone
Abstract: By combining upper echelon theory with meso theory of management, this study investigates the relationship between both corporate and country corruption risk and the performance of CEOs, while controlling for a set of individual-level variables. We used a sample of 455 observations related to 249 listed companies from a list published by the Harvard Business Review of the world's best-performing CEOs, in both developed and emerging countries, over the 5-year period between 2013 and 2017. We implemented hierarchical linear models in a three-level approach based on country- (macro), firm- (meso), and individual-level (micro) variables. We found that corporate corruption risk negatively impacts CEO performance, although this relationship is also significantly moderated by the corruption risk at the country level. Our results support the view that corporate corruption prevention devices play a strong governance role in countries with high corruption risk. By exploring the interplay between these macro- and meso-factors in explaining the micro-level of CEO performance, our paper aims to build a contextualized meso-theory of corruption risk.